LEFT VENTRICULAR REMODELING IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION WITH AND WITHOUT ST SEGMENT ELEVATION - N. E. Zakirova; Z. A. Kazieva; A. N. Zakirova (Столичная издательская компания, 2016)
Aim. To study the remodeling of the left ventricle (LV) in patients with ST segment elevation (STEMI) and non-ST segment elevation (non-STEMI) myocardial infarction (MI). Materials and methods. Patients (n=99) with acute MI (48 - with STEMI, 51 - with non-STEMI) were examined. Diagnosis of MI was set on the basis of the dynamics of myocardial damage markers, data of clinical and electrocardiogram examination. The comparison group consisted of 33 patients with stable angina functional class 2. The control group included 35 healthy men. Structural and functional state of the LV myocardium and types of its remodeling were assessed by echocardiography.Results. It was found that the LV eccentric hypertrophy was the predominated type of LV remodeling in patients with STEMI. Besides, these patients demonstrated disorders of the LV contractile function (LV ejection fraction 40.2±5.49% vs. 61.4±3.91% in control; p<0.05), the LV dilatation (end-systolic volume index 54.1±5.27 vs. 25.2±2.22 ml/m2 in the control; p<0.05), the lowest LV wall thickness (relative wall thickness 0.36±0.01 vs. 0.44±0.01 in control; p<0.05), increase in the LV myocardial stress (168.3±20.17 vs. 108.6±9.82 dynes/cm2 in control; p<0.05), and LV spherification. The majority of patients with non-STEMI revealed combination of concentric and eccentric types of LV remodeling. Their hemodynamic parameters were comparable to those in patients with stable angina, but exceed the control data.Conclusion. In patients with acute MI severity of the LV remodeling correlated with the depth and vastness of myocardial damage. The most significant hemodynamic changes were observed in STEMI.